ANALYSIS OF ADMINISTRATIVE CORRESPONDENCE AT THE ADMINISTRATIVE OFFICE OF PT. NUBIKA JAYA BLOKSONGO SOUTH LABUHAN BATU - Lubis, Septiana Sara; Aslami, Nuri (Transpublika Publisher, 2022)
This research has a goal which is to find out the management of correspondence in PT.Nubika Jaya both incoming and outgoing mail and to find out some of the obstacles that must be faced in managing incoming and outgoing mail. The research method this time uses a descriptive method more precisely, namely a qualitative method. The techniques used are interviews, observation and documentation. The results of this study are about the implementation of correspondence in the administrative Office of PT. Nubika Jaya which has not run optimally due to several activities in mail management that are not in accordance with correspondence procedures, archive storage is only placed on the work desk of the correspondence section, and there are several letter files that are only stacked and tied and then stored on the floor under the table and verbally borrowed by other employees. Still, there is no archive room or special room for storing correspondence as well as the lack of availability of equipment and equipment to manage mail.